Fuel cell catalyst and method for producing same

By using Au-modified Pt nanowire particles in fuel cell catalysts and controlling their structure and composition, the problem of base metal ion leakage is solved, the activity and durability of the catalyst is improved, and the conductivity of the electrolyte and the performance of the fuel cell are ensured.

JP7647252B2Active Publication Date: 2025-03-18KK TOYOTA CHUO KENKYUSHO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021063029
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-01
Publication Date
2025-03-18
Estimated Expiration
2041-04-01

AI Technical Summary

Technical Problem

During use, existing fuel cell catalysts are prone to leakage of base metal ions, resulting in a decrease in catalyst activity and a decrease in proton conductivity of the electrolyte, affecting the performance of the fuel cell.

Method used

Au-modified Pt nanowire particles are used as catalysts, and the Au-modified Pt nanowire particles are controlled to have a high density of support on the electrode material, and their diameters are between 0.8 nm and 10 nm, the mass ratio of Au is between 0.01% and 50%, and the atomic ratio of base metal elements is less than 25%, to reduce the leakage of base metal ions.

Benefits of technology

It effectively improves the activity and durability of fuel cell catalysts, reduces leakage of base metal ions, protects the proton conductivity of the electrolyte, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647252000003
    Figure 0007647252000003
  • Figure 0007647252000004
    Figure 0007647252000004
  • Figure 0007647252000001
    Figure 0007647252000001
Patent Text Reader

Abstract

To provide a fuel cell catalyst high in activity and endurance and small in elution of base metal ions, and a manufacturing method thereof.SOLUTION: A fuel cell catalyst comprises: carriers having conductivity; and Au-modified Pt nanowire particles supported on the surface of the carriers. The Au-modified Pt nanowire particles are 0.8 nm or more and 10 nm or less in short diameter, and 15 mass% or more and 50 mass% or less in the rate of being supported. The Au-modified Pt nanowire particles are 0.01 mass% or more and 50 mass% or less in Au mass percentage, and less than 25 at% in the percentage of atoms of base metal elements. The fuel cell catalyst like this can be obtained by the steps of: synthesizing a Pt nanowire particle precursor with a Pt nanowire particle surface modified with oleylamine; modifying the surface of the Pt nanowire particle precursor with Au; weakly cleaning the resultant Au-modified Pt nanowire particle precursor; causing carriers having conductivity to support, on the surface thereof, the Au-modified Pt nanowire particles; and then, strongly cleaning them.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fuel cell catalyst and a method for producing the same, and more particularly to a fuel cell catalyst which is highly active and durable and which causes little elution of base metal ions, and a method for producing the same. [Background technology]

[0002] A polymer electrolyte fuel cell comprises a membrane electrode assembly (MEA) in which electrodes (catalyst layers) containing a catalyst are bonded to both sides of an electrolyte membrane. A gas diffusion layer is usually disposed on the outside of the catalyst layer. A current collector (separator) having a gas flow path is also disposed on the outside of the gas diffusion layer. A polymer electrolyte fuel cell usually comprises a structure (fuel cell stack) in which a plurality of unit cells each consisting of such an MEA, gas diffusion layer, and current collector are stacked.

[0003] The electrode catalyst for a polymer electrolyte fuel cell is usually one in which catalyst particles are supported on the surface of a carrier. The catalyst particles are made of precious metals such as Pt, Pd, Ru, or alloys containing these metals. Since the electrode reaction occurs on the surface of the catalyst particles, if fine catalyst particles are supported on the surface of the carrier in a highly dispersed manner, the utilization rate of the precious metal is improved, and the amount of expensive precious metal used can be reduced. Therefore, various methods for producing and supporting fine catalyst particles have been proposed.

[0004] For example, Non-Patent Document 1 describes a thin Pt 3 An electrocatalyst in which the surface of Ni nanowires is modified with Au has been disclosed. The same document states: (A)Pt 3 Ni nanowires have higher oxygen reduction reaction (ORR) activity than commercially available Pt / C. (B)Pt 3 The surface modification of Ni nanowires with Au improves their durability (i.e., Pt 3 The reduction of defect sites in the Ni surface layer results in Pt 3The structure and composition of Ni are stabilized and the dissolution of Ni atoms is suppressed), and (C) Such an electrocatalyst has a mass activity of 3.08 A / mg Pt and the area specific activity is 5.74 mA / cm 2 The point that is stated.

[0005] In Non-Patent Document 1, Pt 3 It has been reported that modifying the surface of Ni nanowires with Au improves the specific activity and durability. However, catalysts with a high content of base metal elements, such as those described in Non-Patent Document 1, are highly likely to have the base metal eluted in a fuel cell environment. When the base metal elutes, the activity of the fuel cell catalyst decreases. In addition, when the ions of the eluted base metal are exchanged with protons in the electrolyte, the proton conductivity of the electrolyte decreases, causing a decrease in the performance of the fuel cell. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Zhifu Wu et al., Journal of Materials Chemistry A, 46, 2019 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a fuel cell catalyst which is highly active and durable and which causes little elution of base metal ions, and a method for producing the same. Another problem that the present invention aims to solve is to provide a fuel cell catalyst and a method for producing the same, in which Au-modified Pt nanowire particles are densely supported on the surface of a support, there is little aggregation of the nanowire particles, and there is little decrease in activity due to catalyst poisoning. [Means for solving the problem]

[0008] In order to solve the above problems, the fuel cell catalyst according to the present invention has the following configuration. (1) The fuel cell catalyst is A conductive carrier; Au-modified Pt nanowire particles supported on the support surface; It is equipped with: (2) The Au-modified Pt nanowire particles are The short diameter is 0.8 nm or more and 10 nm or less, The loading rate is 15 mass% or more and 50 mass% or less. (3) The Au-modified Pt nanowire particles have a mass percentage of Au of 0.01 mass % or more and 50 mass % or less. Here, the "mass ratio of Au" refers to the total mass (M T ) versus the mass of Au (M Au ) ratio (=M Au ×100 / M T ) (4) The Au-modified Pt nanowire particles have an atomic ratio of base metal elements of less than 25 at %. Here, the "atomic ratio of base metal elements" refers to the number of Pt atoms (N Pt ) and the number of atoms of the base metal element (N BM ) to the sum of the number of atoms of the base metal element (N BM ) ratio (=N BM ×100 / (N Pt +N BM ))

[0009] The method for producing a fuel cell catalyst according to the present invention has the following features. (1) The method for producing the fuel cell catalyst comprises the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; A second step of obtaining a Pt nanowire particle precursor in which the surface of the Pt nanowire particle is modified with the oleylamine by maintaining the precursor solution at a temperature of 160° C. or more and 190° C. or less; a third step of cooling the precursor solution in which the Pt nanowire particle precursor has been produced to a temperature of 100° C. or less, adding an Au precursor solution to the precursor solution, and maintaining the temperature at 120° C. or more and 190° C. or less to obtain an Au-modified Pt nanowire particle precursor in which the surfaces of the Pt nanowire particles are modified with Au; a fourth step of washing the Au-modified Pt nanowire particle precursor to obtain Au-modified Pt nanowire particles from which a portion of the oleylamine modifying the outermost surface has been removed; a fifth step of supporting the Au-modified Pt nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the Au-modified Pt nanowire particles supported on the surface of the support; a sixth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the Au-modified nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with: (2) The fourth step comprises washing the Au-modified Pt nanowire particle precursor once with ethanol or a cyclohexane / ethanol mixed solvent. (3) The sixth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins.

[0010] The first step may further comprise dissolving or dispersing a base metal element precursor in the oleylamine. Furthermore, the method may further include, after the sixth step, a seventh step of treating the fuel cell catalyst with an acid to dissolve all or a part of the base metal elements contained in the fuel cell electrode catalyst. Effect of the Invention

[0011] By making the content of base metal elements contained in the Au-modified Pt nanowire particles less than 25 at%, it is possible to suppress the decrease in proton conductivity of the electrolyte caused by the elution of ions of the base metal elements. Furthermore, by modifying the surface of Pt nanowire particles with a base metal content of less than 25 at% with Au, the activity and activity retention rate are improved.

[0012] By performing relatively weak washing after the synthesis of the Au-modified nanowire particles, the surface modifier oleylamine is not excessively removed, which can suppress the aggregation of the Au-modified nanowire particles, and therefore the Au-modified nanowire particles can be densely supported on the support surface without agglomeration. In addition, after the Au-modified nanowire particles are supported on the support surface, the remaining surface modifier can be almost completely removed by performing a relatively strong washing, thereby preventing catalyst poisoning caused by the remaining surface modifier.

[0013] Furthermore, when Au-modified nanowire particles are synthesized using a raw material containing a base metal element precursor, the Au-modified nanowire particles are supported on a support surface, and then the support surface is washed with an acid to remove all or part of the base metal elements remaining in the fuel cell catalyst, thereby making it possible to suppress the elution of the base metal elements from the catalyst in a fuel cell environment. [Brief description of the drawings]

[0014] [Figure 1] 1 is a TEM image of the fuel cell catalyst obtained in Example 1. [Diagram 2] 1 is a TEM image of the fuel cell catalyst obtained in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An embodiment of the present invention will be described in detail below. [1. Fuel cell catalyst] The fuel cell catalyst according to the present invention (hereinafter, simply referred to as "catalyst") is A conductive carrier; Au-modified Pt nanowire particles supported on the support surface; It is equipped with:

[0016] [1.1. Carrier] The carrier is made of a conductive material. There is no particular limitation on the material of the carrier, so long as it is conductive and usable in the fuel cell operating environment. Examples of the material of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.

[0017] [1.2. Au-modified Pt nanowire particles] [1.2.1. Shape] In the present invention, the term "Au-modified Pt nanowire particles" refers to particles having a wire-like elongated shape, a diameter of nanometer size, and a composition that satisfies the conditions described below. By using the method described below, nanowire particles having a short diameter of more than 0.8 nm and not more than 10 nm can be obtained. When the manufacturing conditions are optimized, the short diameter becomes greater than 0.8 nm and equal to or less than 3 nm. Similarly, when the manufacturing conditions are optimized, the length is 10 nm or more and 50 nm or less.

[0018] [1.2.2. Composition] In the present invention, the Au-modified Pt nanowire particles contain Pt and Au, and optionally a base metal element.

[0019] [A. Mass ratio of Au] The "mass ratio of Au" refers to the total mass of the Au-modified Pt nanowire particles (M T ) versus the mass of Au (M Au ) ratio (=M Au ×100 / M T )

[0020] In general, the higher the mass ratio of Au, the higher the mass activity of the Au-modified Pt nanowire particles. To obtain such an effect, the mass ratio of Au must be 0.01 mass% or more. The mass ratio of Au is preferably 0.1 mass% or more, and more preferably 1.0 mass% or more. On the other hand, if the mass ratio of Au becomes excessive, the electrochemically effective surface area (ECSA) decreases. Therefore, the mass ratio of Au needs to be 50 mass% or less. The mass ratio of Au is preferably 20 mass% or less, and more preferably 10 mass% or less.

[0021] [B. Atomic ratio of base metal elements] The "atomic ratio of base metal elements" refers to the number of Pt atoms (N Pt ) and the number of atoms of base metal elements (N BM ) for the number of atoms of base metal elements (N BM ) ratio (=N BM ×100 / (N Pt +N BM ))

[0022] Certain base metal elements have the effect of highly activating Pt nanowire particles, so the Au-modified Pt nanowire particles may contain a base metal element. For example, Ni has the effect of highly activating Pt nanowire particles through the alloying effect and surface control. Other base metal elements that exhibit this effect include Co, for example.

[0023] However, if the atomic ratio of the base metal element is excessive, there is a risk that a large amount of the base metal element will be eluted when the catalyst is used in a fuel cell environment. Furthermore, if the atomic ratio of the base metal element is excessive, there is a risk that the mass activity retention rate will decrease. In order to suppress the elution of the base metal element and the decrease in the mass activity retention rate, the atomic ratio of the base metal element needs to be less than 25 at%. The atomic ratio of the base metal element is preferably 20 at% or less.

[0024] [1.2.3. Loading rate] "Loading ratio" refers to the ratio of the mass of the Au-modified Pt nanowire particles to the total mass of the catalyst. In general, if the loading rate is too low, the amount of Pt per unit volume when a membrane electrode assembly (MEA) is produced will be small. Therefore, the thickness of the catalyst layer required to ensure a sufficient amount of Pt for power generation will be large. In general, the thicker the catalyst layer, the greater the resistance to mass transfer within the catalyst layer. Therefore, the loading rate must be 15 mass% or more. The loading rate is preferably 20 mass% or more, and more preferably 30 mass% or more. On the other hand, even if the loading rate is increased more than necessary, there is no difference in the effect and no practical benefit. Therefore, the loading rate must be 50 mass% or less.

[0025] [1.3. Characteristics] [1.3.1. ECSA (Electrochemically Effective Surface Area)] The fuel cell catalyst according to the present invention has a high ECSA because the Au-modified Pt nanowire particles are densely supported on the support surface and the Au-modified Pt nanowire particles are less likely to aggregate. 2 / g Pt More than 200m 2 / g Pt Further optimization of the production conditions results in a catalyst with an ECSA of 70m 2 / g Pt or more than 100m 2 / g Pt That's all.

[0026] [1.3.2. MA (activity per Pt mass)] The Au-modified Pt nanowire particles have a nanometer-sized diameter, a large surface area per Pt mass, and a high density of highly active (111) faces, so they exhibit high MA. When the manufacturing conditions were optimized, the MA was increased to 500 A / g Pt More than 30000A / g Pt Further optimization of the preparation conditions results in a catalyst with a molecular weight of 875 A / g or less. Pt or more than 1250A / g PtThat's all.

[0027] [1.3.3. SA (specific activity)] The fuel cell catalyst according to the present invention exhibits high SA. When the production conditions are optimized, the SA can reach 2000 μA / cm 2 More than 15000μA / cm 2 Further optimization of the preparation conditions results in a catalyst with an SA of 2200 μA / cm 2 or more, or 2500μA / cm 2 That's all.

[0028] [1.3.4. Mass activity maintenance rate] "Mass activity retention rate (%)" refers to the mass activity (MA 0 The ratio of mass activity (MA) after durability test to mass activity (MA) (=MA × 100 / MA 0 ) The "durability test" refers to a test in which the glassy carbon coated with the fuel cell catalyst according to the present invention was used as the working electrode, and an oxygen-saturated electrolyte (0.1M HClO 4 ) in which a potential sweep from 0.4V to 1.0V (RHE standard, held for 3s at each potential) is performed for 2000 cycles.

[0029] The catalyst according to the present invention has a high mass activity retention rate because the surface of the Pt nanowire particles is modified with Au. When the manufacturing conditions are optimized, the mass activity retention rate is 50% or more. When the manufacturing conditions are further optimized, the mass activity retention rate is 55% or more.

[0030] [2. Manufacturing method of fuel cell catalyst] The method for producing a fuel cell catalyst according to the present invention includes the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; A second step of obtaining a Pt nanowire particle precursor in which the surface of the Pt nanowire particle is modified with the oleylamine by maintaining the precursor solution at a temperature of 160° C. or more and 190° C. or less; a third step of cooling the precursor solution in which the Pt nanowire particle precursor has been produced to a temperature of 100° C. or less, adding an Au precursor solution to the precursor solution, and maintaining the temperature at 120° C. or more and 190° C. or less to obtain an Au-modified Pt nanowire particle precursor in which the surfaces of the Pt nanowire particles are modified with Au; a fourth step of washing the Au-modified Pt nanowire particle precursor to obtain Au-modified Pt nanowire particles from which a portion of the oleylamine modifying the outermost surface has been removed; a fifth step of supporting the Au-modified Pt nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the Au-modified Pt nanowire particles supported on the surface of the support; a sixth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the Au-modified nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with:

[0031] The method for producing a fuel cell catalyst according to the present invention may further include a seventh step, after the sixth step, of treating the fuel cell catalyst with an acid to dissolve all or a portion of the base metal elements contained in the fuel cell electrode catalyst.

[0032] [2.1. 1st step] First, the Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a nitrogen-containing surfactant are dissolved or dispersed in oleylamine to obtain a precursor solution (first step). The first step may further comprise dissolving or dispersing a base metal element precursor in the oleylamine.

[0033] 2.1.1. Ingredients The Pt precursor is the main raw material of the nanowire particles. The type of Pt precursor is not particularly limited as long as it can synthesize the nanowire particles. Examples of Pt precursors include platinum(II) acetylacetonate (Pt(acac) 2 ), chloroplatinic acid (H 2 PtCl6 ), tetraammineplatinum chloride (Pt(NH 3 ) 4 Cl 2 ) etc.

[0034] The base metal element precursor is an effective component for high activation of nanowire particles, and can be added as necessary. If the precursor solution does not contain a strong reducing agent (e.g., glucose), the base metal element precursor is usually not reduced, and nanowire particles consisting essentially of Pt alone are obtained. However, depending on the synthesis conditions, base metal elements or compounds of base metal elements may be by-produced. The type of base metal element precursor is not particularly limited as long as it is capable of synthesizing nanowire particles. For example, an example of a base metal element precursor containing Ni is Ni(II) acetylacetonate (Ni(acac) 2 ), Nickel chloride (NiCl 2 ), nickel acetate (Ni(CH 3 COO) 2 ) etc.

[0035] W(CO) 6 and Mo(CO) 6 is a component necessary for controlling the length and surface roughness of nanowire particles. The precursor solution contains W(CO) 6 or Mo(CO) 6 Either one of them may be included, or both may be included. The precursor solution is W(CO) 6 and / or Mo(CO) 6 When W(CO) is added, 6 Also Mo(CO) 6 CO is released from the nanowire. The released CO is repeatedly adsorbed and desorbed on the surface of the nanowire particle during growth. As a result, it is thought that the length of the nanowire particle and the surface roughness are controlled.

[0036] Nitrogen-containing surfactants are necessary components for growing Pt into wires. It is believed that the addition of nitrogen-containing surfactants to the precursor solution produces rod-like micelles, and the Pt precursor is reduced within the rod-like micelles, facilitating the production of nanowire particles. The type of nitrogen-containing surfactant is not particularly limited as long as it is capable of synthesizing nanowire particles. Examples of nitrogen-containing surfactants include cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), and dodecyltrimethylammonium bromide (DDAB).

[0037] Oleylamine is (a) a solvent for dissolving the raw materials; (b) a reducing agent for reducing the Pt precursor, and (c) A surface modifier that adsorbs to the surface of nanowire particles and prevents the nanowire particles from agglomerating. It functions as: However, since the reducing power of oleylamine is relatively weak, the reduction of the Pt precursor proceeds but the reduction of the base metal element precursor usually does not proceed at all.

[0038] [2.1.2. Concentration] The concentration of each component contained in the precursor solution is not particularly limited, and an optimal concentration can be selected depending on the purpose. Generally, if the concentration of the Pt precursor is too low, the yield of nanowire particles is low, so the concentration of the Pt precursor is preferably 0.24 mass% or more. On the other hand, even if the concentration of the Pt precursor is made higher than necessary, there is no difference in the effect and no practical benefit, so the concentration of the Pt precursor is preferably 0.48 mass% or less.

[0039] In the case of adding a base metal element precursor to the raw material, generally, if the concentration of the base metal element precursor is too low, the high activation of the nanowire particles due to the alloying effect and surface control may not be obtained. Therefore, the concentration of the base metal element precursor is preferably 0.01 mass% or more. On the other hand, if the concentration of the base metal element precursor is too high, the amount of the base metal element that is reduced increases, so the concentration of the base metal element precursor is preferably 0.15 mass% or less.

[0040] In general, W(CO) 6 and Mo(CO) 6 If the total concentration of W(CO) is too low, nanowire particles cannot be recovered. 6 and Mo(CO) 6 The total concentration is preferably 0.07 mass% or more. On the other hand, W(CO) 6 and Mo(CO) 6 Even if the total concentration of W(CO) is increased more than necessary, there is no difference in the effect and no practical benefit. 6 and Mo(CO) 6 The total concentration is preferably 0.7 mass% or less.

[0041] In general, the higher the concentration of the nitrogen-containing surfactant, the easier it is to form rod-like micelles, which in turn makes it easier for Pt to grow into nanowires. To achieve this effect, the concentration of the nitrogen-containing surfactant is preferably 0.39 mass% or more. On the other hand, if the concentration of the nitrogen-containing surfactant is made higher than necessary, there is no difference in the effect and no practical benefit, and therefore the concentration of the nitrogen-containing surfactant is preferably 3.0 mass% or less.

[0042] [2.2. 2nd process] Next, the precursor solution is maintained at a temperature of 160° C. or more and 190° C. or less (second step), whereby Pt nanowire particle precursors in which the surfaces of Pt nanowire particles are modified with oleylamine are obtained. Here, "Pt nanowire particles" refers to particles having a wire-like shape and a Pt content of more than 75 at %. That is, in the present invention, the term "Pt nanowire particles" includes not only nanowire particles consisting of Pt alone, but also nanowire particles consisting of a Pt-M alloy in which the content of the base metal element M is less than 25 at %.

[0043] If the treatment temperature is too low, the reduction reaction does not proceed, so the treatment temperature is preferably 160° C. or higher. On the other hand, if the treatment temperature is too high, the proportion of spherical particles produced as by-products may increase, so the treatment temperature is preferably 190° C. or lower.

[0044] If the treatment time is too short, the percentage of Pt nanowire particles obtained decreases, so the treatment time is preferably 2 hours or more. On the other hand, if the treatment time is longer than necessary, there is no difference in the effect and no practical benefit, so it is preferable to select an optimal treatment time depending on the purpose.

[0045] [2.3. Third step] Next, the precursor solution in which the Pt nanowire particle precursor is produced is cooled to a temperature of 100° C. or less, and then the Au precursor solution is further added to the precursor solution, which is then maintained at a temperature of 120° C. or more and 190° C. or less (third step). This produces an Au-modified Pt nanowire particle precursor in which the surfaces of the Pt nanowire particles are modified with Au. Here, the term "Au-modified Pt nanowire particle precursor" refers to Au-modified Pt nanowire particles having oleylamine adsorbed on the outermost surface thereof. The term "Au-modified Pt nanowire particles" refers to Pt nanowire particles having Au precipitated on a portion of the surface thereof.

[0046] The Au precursor is not particularly limited as long as it contains Au and is capable of modifying the surface of the Pt nanowire particles with Au. Examples of the Au precursor include HAuCl 4 , KAuBr 4 , AuBr 3 , Au(acac) 3 etc. The Au precursor is dissolved or dispersed in a suitable solvent to prepare an Au precursor solution. The Au precursor solution is added to the precursor solution containing the Pt nanowire particle precursor after the precursor solution is cooled to a temperature of 100° C. or less. This is because if the Au precursor solution is added to a high-temperature precursor solution, the Au precursor reacts violently in the solution, and the surface of the Pt nanowire particle may not be modified with Au.

[0047] The Au precursor solution is added to a precursor solution containing Pt nanowire particle precursors, and then the mixture is maintained at a predetermined temperature for a predetermined time. Generally, if the treatment temperature is too low, the Au precursor is difficult to reduce. Therefore, the treatment temperature is preferably 120° C. or higher. The treatment temperature is more preferably 140° C. or higher, and even more preferably 160° C. or higher. On the other hand, if the treatment temperature is too high, Au may precipitate independently as coarse particles. Therefore, the treatment temperature is preferably 190° C. or less. The treatment temperature is more preferably 180° C. or less, and even more preferably 170° C. or less.

[0048] If the treatment time is too short, the reduction of the Au precursor may not be completed. Therefore, the treatment time is preferably 30 minutes or more. The treatment time is more preferably 60 minutes or more, and even more preferably 90 minutes or more. On the other hand, if the treatment time is longer than necessary, there is no difference in the effect and no practical benefit, so it is preferable to select an optimal treatment time depending on the purpose.

[0049] [2.4. 4th step] Next, the Au-modified Pt nanowire particle precursor is washed to obtain Au-modified Pt nanowire particles from which a portion of the oleylamine modifying the outermost surface has been removed (fourth step).

[0050] Oleylamine is a necessary component for forming Pt nanowire particles, but it is also a substance that poisons the active sites of the catalyst. In order to reduce catalyst poisoning, it is preferable to completely remove oleylamine from the surface of the Au-modified Pt nanowire particles. However, oleylamine also functions as a surface modifier that suppresses the aggregation of the Au-modified Pt nanowire particles generated in the solution. Therefore, if the Au-modified Pt nanowire particles are washed under conditions that remove all of the oleylamine that modifies the surface of the Au-modified Pt nanowire particles before being supported on the support surface after the reaction is completed, the Au-modified Pt nanowire particles are likely to aggregate.

[0051] Therefore, the washing before loading the Au-modified Pt nanowire particle precursor on the support surface must be performed under conditions that remove by-products and unreacted materials and remove a part of the oleylamine that modifies the surface of the Au-modified Pt nanowire particle. In the present invention, the washing before loading is performed only once using ethanol or a cyclohexane / ethanol mixed solvent. This is different from the conventional method. Ethanol and cyclohexane / ethanol mixed solvents both have a moderate cleaning power, so washing with ethanol or cyclohexane / ethanol mixed solvents multiple times will remove too much oleylamine. Therefore, washing before loading is performed only once.

[0052] When using a cyclohexane / ethanol mixed solvent as a cleaning solvent, the content of cyclohexane in the mixed solvent is selected to be optimal depending on the purpose. In general, the higher the cyclohexane content, the stronger the cleaning power. To obtain such an effect, the cyclohexane content is preferably 10 vol% or more. On the other hand, even if the content of cyclohexane is increased more than necessary, there is no difference in the effect and no practical benefit, so the content of cyclohexane is preferably 50 vol% or less.

[0053] [2.5. 5th step] Next, the Au-modified Pt nanowire particles are supported on the surface of a conductive support (step 5), thereby obtaining a catalyst precursor in which the Au-modified Pt nanowire particles are supported on the surface of the support.

[0054] The method of supporting the Au-modified Pt nanowire particles on the carrier surface is not particularly limited. For example, when the Au-modified Pt nanowire particle precursor and the carrier are dispersed in a solvent and irradiated with ultrasonic waves, the Au-modified Pt nanowire particle precursor and the carrier are uniformly dispersed, and at the same time, the oleylamine on the surface of the Au-modified Pt nanowire particles is gradually removed by the solvent. Furthermore, when most of the oleylamine on the surface of the Au-modified Pt nanowire particles is removed, the Au-modified Pt nanowire particles are attached onto the carrier. As a result, the Au-modified Pt nanowire particles can be supported on the carrier surface.

[0055] [2.6. 6th step] Next, the catalyst precursor is washed to further remove the oleylamine remaining on the surface of the Au-modified nanowire particles (step 6), thereby obtaining the fuel cell catalyst according to the present invention.

[0056] As mentioned above, oleylamine is a surface modifier for suppressing aggregation, and at the same time, it is also a substance that causes catalyst poisoning. In order to reduce catalyst poisoning, it is preferable to wash the Au-modified Pt nanowire particles after they are supported on the support surface under conditions that allow the oleylamine remaining on the surface of the Au-modified Pt nanowire particles to be almost completely removed. "Almost completely removed" means that the SA of the catalyst after washing is 2000 μA / cm 2 This means that the above is the case. In the present invention, the catalyst precursor is washed three or more times after the loading with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins, which is different from the conventional method.

[0057] Hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins all have stronger cleaning power than the cyclohexane / ethanol mixed solvent, so washing the catalyst precursor with these solvents can remove most of the remaining oleylamine. The above solvents have strong cleaning power, so that a sufficient effect can be obtained even with one cleaning. However, generally, the more the number of cleanings, the less the amount of oleylamine remaining. In order to reduce catalyst poisoning, the number of cleanings must be three or more. The number of cleanings is preferably five or more.

[0058] [2.7. 7th step] Next, if necessary, the fuel cell catalyst is subjected to an acid treatment (seventh step), which makes it possible to elute all or a part of the base metal elements contained in the fuel cell catalyst.

[0059] Oleylamine also functions as a reducing agent, but its reducing power is relatively weak. Therefore, when a base metal element precursor is added to the precursor solution, the base metal element precursor in the precursor solution is usually hardly reduced unless a stronger reducing agent is further added or the reaction is carried out at a higher temperature. However, depending on the manufacturing conditions, base metal elements or base metal element compounds may be mixed into the catalyst. Base metal elements alloyed with Pt may improve the catalytic activity of Pt, but the base metal elements, base metal element compounds, and base metal elements alloyed with Pt contained in the catalyst may easily dissolve in the fuel cell environment and cause cationic contamination. In order to suppress the dissolution of base metal elements, it is preferable to previously wash the catalyst with an acid to remove the remaining base metal elements.

[0060] The conditions of the acid treatment are not particularly limited as long as the remaining base metal elements can be removed. For example, most of the remaining base metal elements can be removed by adding the fuel cell catalyst to a 1M aqueous sulfuric acid solution and stirring for 12 hours. After the acid treatment, the fuel cell catalyst is recovered, washed and dried.

[0061] [3. Effect] [3.1. Improvement of catalytic activity by Au modification] In Non-Patent Document 1, Pt 3 It has been reported that modifying the surface of Ni nanowires with Au improves the specific activity and durability. However, catalysts with a high content of base metal elements, such as those described in Non-Patent Document 1, are highly likely to dissolve the base metal elements in a fuel cell environment. When the base metal elements dissolve, the activity of the fuel cell catalyst decreases. In addition, when the ions of the dissolved base metal elements are exchanged with protons in the electrolyte, the proton conductivity of the electrolyte decreases, causing a decrease in the performance of the fuel cell.

[0062] In contrast, when the content of the base metal element contained in the Au-modified Pt nanowire particles is set to less than 25 at %, it is possible to suppress the decrease in proton conductivity of the electrolyte caused by the elution of ions of the base metal element. In addition, when the surface of Pt nanowire particles with a base metal content of less than 25 at% is modified with Au, the activity and activity retention rate are improved. This is thought to be because Au protects the edges, suppressing Pt dissolution from the unstable edges.

[0063] [3.2. Suppression of nanowire particle aggregation] Oleylamine functions as a surface modifier that prevents the aggregation of nanowire particles. After synthesizing nanowire particles in the presence of oleylamine, washing the nanowire particles three times with a cyclohexane / ethanol mixed solvent results in excessive removal of oleylamine from the nanowire particle surface. This makes it difficult to suppress the aggregation of nanowire particles, and makes it difficult to support nanowire particles on the support surface at high density and high dispersion.

[0064] Next, even if the nanowire particles are supported on the support surface and washed three times with a cyclohexane / ethanol mixed solvent, the oleylamine remaining on the surface of the nanowire particles cannot be completely removed. The remaining oleylamine blocks (poisons) the active sites of the catalyst, causing a decrease in catalytic activity. Furthermore, when base metal element precursors are used to highly activate nanowire catalysts through alloying effects and surface control, base metal elements or compounds of base metal elements may be included in the catalyst depending on the manufacturing conditions. Base metal elements, compounds of base metal elements, and base metal elements alloyed with Pt are easily dissolved in the fuel cell environment, causing cationic contamination.

[0065] In contrast, if the nanowire particles are synthesized and then washed relatively weakly, the surface modifier oleylamine is not removed excessively, thereby suppressing the aggregation of the nanowire particles, and the nanowire particles can be densely supported on the support surface without agglomeration. In addition, by performing relatively strong washing after supporting the nanowire particles on the support surface, the remaining surface modifier can be almost completely removed, thereby suppressing catalyst poisoning caused by the remaining surface modifier.

[0066] Furthermore, by carrying out acid washing after supporting the nanowire particles on the support surface, the base metal elements remaining in the fuel cell catalyst can be almost completely removed, thereby preventing the base metal elements from eluting from the catalyst in the fuel cell environment. EXAMPLES

[0067] (Examples 1-2, Comparative Examples 1-2) [1. Sample preparation] [1.1. Examples 1 to 2] Pt(acac) 2 , Mo(CO) 6 , and a nitrogen-containing surfactant were added to oleylamine and ultrasonically dispersed for 1 hour to obtain precursor solution A. Separately, HAuCl 4 was added to oleylamine and ultrasonically dispersed for 1 hour to obtain precursor solution B. The temperature of the precursor solution A was raised from room temperature to 160° C. at a rate of 10° C. / min, and then maintained at 160° C. for 2 hours. This resulted in a colloidal solution in which Pt nanowire particles were dispersed.

[0068] Next, the temperature of the colloidal solution was lowered to 100°C, and then precursor solution B was added to the colloidal solution. The amount of precursor solution B was set so that the mass ratio of Au in the colloidal solution was 15 mass% (Example 1) or 50 mass% (Example 2). Next, the solution was heated again to 160°C and held at 160°C for 2 hours. This resulted in a colloidal solution in which Au-modified Pt nanowire particles, in which the surfaces of Pt nanowire particles were modified with Au, were dispersed. The Au-modified Pt nanowire particles were recovered from the colloidal solution and washed once with ethanol to remove unreacted materials and a portion of the surface modifier (oleylamine).

[0069] Next, the washed Au-modified Pt nanowire particles were redispersed in hexane to obtain Dispersion A. In addition, the carbon support was dispersed in hexane to obtain Dispersion B. Dispersion A was added to Dispersion B, and ultrasonic irradiation was performed for 1 hour to support the Au-modified Pt nanowire particles on the carbon support surface. Furthermore, the Au-modified Pt nanowire particle-supported carbon (hereinafter also referred to as "nanowire particle / C") was recovered from the dispersion and the nanowire particle / C was washed five times with hexane. The solid matter was then filtered and dried to obtain the catalyst.

[0070] [1.2. Comparative Example 1] A catalyst was obtained in the same manner as in Example 1, except that precursor solution B was not used.

[0071] [1.3. Comparative Example 2] The Ni precursor is Ni(acac) 2 The precursor solution A was mixed with Ni(acac) so that the atomic ratio of Pt:Ni was 1:1. 2 The obtained precursor solution A was reacted under a predetermined condition to obtain a colloidal solution in which nanowire particles made of Pt-Ni alloy were dispersed. Thereafter, a catalyst was obtained in the same manner as in Example 1. However, the amount of precursor solution B added was set to an amount such that the mass ratio of Au in the colloidal solution was 8 mass%.

[0072] 2. Test Method [2.1. TEM observation and composition analysis] The catalyst was observed using a transmission electron microscope (TEM). In addition, the composition of the obtained catalyst was analyzed using an inductively coupled plasma mass spectrometer (ICP-MS).

[0073] [2.2. Electrochemical evaluation] [2.2.1. Mass activity] The catalyst was electrochemically evaluated using a rotating disk electrode (RDE). The cell was a three-electrode type, and the electrolyte was 0.1M HClO 4 The working electrode was made of glassy carbon coated with a catalyst. The reference electrode and counter electrode were a reversible hydrogen electrode (RHE) and a black Pt mesh, respectively. The working electrode was immersed in an electrolyte saturated with Ar, and a potential sweep was performed between 0.05 V and 1.2 V (RHE). The potential sweep was performed until the shape of the cyclic voltammogram (CV) became stable. The electrolyte was then replaced with O 2 The electrodes were saturated with 1000 volts of platinum and rotated at 1600 rpm while linear sweep voltammetry (LSV, positive potential sweep, sweep rate: 10 mV / s) was performed. The mass activity (MA) of each sample was calculated by dividing the obtained LSV current value at 0.9 V by the platinum mass.

[0074] [2.2.2. Durability test] After the initial activity evaluation, a durability test was conducted by repeating a potential sweep from 0.4 V to 1.0 V (based on RHE, held at each potential for 3 s) for 2000 cycles in an oxygen-saturated electrolyte (0.1 M HClO4). For each sample, the mass activity (MA) at 0.9 V was determined before and after the durability test. 0 The ratio of mass activity (MA) after durability test to mass activity (MA) (=MA × 100 / MA 0 ) was calculated as the activity retention rate.

[0075] [3. Results] [3.1. TEM observation and composition analysis] Figure 1 shows a TEM image of the fuel cell catalyst obtained in Example 1. Figure 2 shows a TEM image of the fuel cell catalyst obtained in Example 2. Figures 1 and 2 show that the Au-modified Pt nanowire particles are highly dispersed and supported on the support surface. The amount of the Au precursor charged and the abundance ratio of each element (analysis value by ICP-MS) are shown in Table 1. It can be seen from Table 1 that the amount ratio of Au to Pt increases as the amount of Au charged increases.

[0076] [Table 1]

[0077] [3.2. Electrochemical evaluation] Table 2 shows the electrochemical effective surface area (ECSA), mass activity (MA), specific activity (SA), and mass activity retention rate. (a) The activities of Examples 1 and 2 are higher than that of Comparative Example 1; and (b) The mass activity retention rates of Examples 1 and 2 are higher than those of Comparative Examples 1 and 2. The reason why the mass activity retention rate of Comparative Example 2 is low is believed to be because the Ni content exceeds 25 at %. From the above, it has been found that the present invention can provide a highly active and highly durable catalyst.

[0078] [Table 2]

[0079] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0080] The fuel cell catalyst according to the present invention can be used as an electrode catalyst for the air electrode and / or fuel electrode of a polymer electrolyte fuel cell used in, for example, a power source for an automobile or a small stationary generator.

Claims

1. A fuel cell catalyst comprising: (1) The fuel cell catalyst is A conductive carrier; Au-modified Pt nanowire particles supported on the support surface; It is equipped with: (2) The Au-modified Pt nanowire particles are The minor axis is 0.8 nm or more and 10 nm or less, The loading rate is 15 mass % or more and 50 mass % or less. (3) The Au-modified Pt nanowire particles have a mass percentage of Au of 0.01 mass % or more and 50 mass % or less. Here, the "mass ratio of Au" refers to the total mass (M T ) to the mass of Au (M Au ) ratio (= M Au x 100 / M T ) (4) The Au-modified Pt nanowire particles have an atomic ratio of base metal elements of less than 25 at %. Here, the "atomic ratio of base metal elements" refers to the number of Pt atoms (N Pt ) and the number of atoms of the base metal element (N BM The number of atoms of the base metal element (N BM ) ratio (= N BM ×100 / (N Pt +N BM )).

2. ECSA (electrochemical effective surface area) is 40m 2 / g Pt More than 200m 2 / g Pt 2. The fuel cell catalyst of claim 1, wherein:

3. MA (activity per Pt mass) is 500 A / g Pt More than 30000A / g Pt 3. The fuel cell catalyst according to claim 1, wherein:

4. SA (specific activity) is 2000 μA / cm 2 More than 15000μA / cm 2 4. The fuel cell catalyst according to claim 1, wherein:

5. 5. The fuel cell catalyst according to claim 1, which has a mass activity retention rate of 50% or more. Here, the "mass activity retention rate (%)" refers to the ratio of the mass activity (MA) after the durability test to the mass activity (MA) before the durability test (=MA×100 / MA0), The "durability test" refers to a test in which glassy carbon coated with the fuel cell catalyst was used as the working electrode, and a potential sweep of 0.4 V to 1.0 V (RHE standard, held at each potential for 3 s) was performed 2,000 cycles in an oxygen-saturated electrolyte (0.1 M HClO 4 ).

6. A method for producing a fuel cell catalyst comprising the following steps: (1) The method for producing the fuel cell catalyst includes the steps of: Pt precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dissolving or dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; A second step of obtaining a Pt nanowire particle precursor in which the surface of the Pt nanowire particle is modified with the oleylamine by maintaining the precursor solution at a temperature of 160° C. or more and 190° C. or less; a third step of cooling the precursor solution in which the Pt nanowire particle precursor is produced to a temperature of 100° C. or less, adding an Au precursor solution to the precursor solution, and maintaining the temperature at 120° C. or more and 190° C. or less to obtain an Au-modified Pt nanowire particle precursor in which the surfaces of the Pt nanowire particles are modified with Au; a fourth step of washing the Au-modified Pt nanowire particle precursor to obtain Au-modified Pt nanowire particles from which a part of the oleylamine modifying the outermost surface has been removed; a fifth step of supporting the Au-modified Pt nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the Au-modified Pt nanowire particles supported on the surface of the support; a sixth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the Au-modified nanowire particles, thereby obtaining the fuel cell catalyst according to any one of claims 1 to 5; It is equipped with: (2) The fourth step comprises washing the Au-modified Pt nanowire particle precursor once with ethanol or a cyclohexane / ethanol mixed solvent. (3) The sixth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of hexane, aromatic hydrocarbons, cycloparaffins, and n-paraffins.

7. The first step further comprises dissolving or dispersing a base metal element precursor in the oleylamine, When the atomic ratio of the base metal element in the fuel cell catalyst obtained in the sixth step is 25 at% or more, the method further includes a seventh step, which is performed after the sixth step, of treating the fuel cell catalyst with an acid to dissolve all or a part of the base metal element contained in the fuel cell electrode catalyst. The method for producing the fuel cell catalyst according to claim 6 .

Citation Information

Patent Citations

  • Platinum and platinum-based alloy nanotubes used as electrocatalysts for fuel cells

    JP2009527890A

  • Catalyst for fuel cell and method of producing the same

    JP2021026961A